The Real Issues of the Middle East and the Arab Spring Addressing Research, Innovation and Entrepreneurship - Andersson, Thomas; Djeflat, Abdelkader; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
The wave of protests and populist uprisings in the Middle East has heightened the focus on a volatile region. But the emphasis on political issues has obscured underlying issues concerning education, infrastructure, research, innovation, entrepreneurship and sustainable environmental and social development. This volume, emerging in the aftermath of a conference and workshop on science and technology in the region, presents contributions from a range of experts from the Middle East, Europe, and the world to provide fresh new insights and perspectives on the challenges and prospects for regional development in the changing global context of our time. The authors explore such topics as: the role of information and communication technologies; mindset change in support of investment in intangible assets and risk-taking; how to approach cultural issues, institutions and governance; collaborations with other regions, and; benchmarking performance while drawing lessons of relevance for the special local context. Ultimately, they offer a number of precise policy recommendations and practical insights for creating an enabling environment for capturing economic, political, and social opportunity.
Keywords: Economics; Development Economics; Economic policy; Entrepreneurship; Economics/Management Science; R & D/Technology Policy; Entrepreneurship; Economic Policy; Development Economics